Genetics and Molecular Biology of the Electron Flow for Sulfate Respiration in Desulfovibrio - Keller, Kimberly L.; Wall, Judy D. (Frontiers in Microbiology, 2011)
Progress in the genetic manipulation of the Desulfovibrio strains has provided an opportunity to explore electron flow pathways during sulfate respiration. Most bacteria in this genus couple the oxidation of organic acids or ethanol with the reduction of sulfate, sulfite, or thiosulfate. Both fermentation of pyruvate in the absence of an alternative terminal electron acceptor, disproportionation of fumarate and growth on H2 with CO2 during sulfate reduction are exhibited by some strains. The ability to produce or consume H2 provides Desulfovibrio strains the capacity to participate as either partner in interspecies H2 transfer. Interestingly the mechanisms of energy conversion, pathways of electron flow and the parameters determining the pathways used remain to be elucidated. Recent application of molecular genetic tools for the exploration of the metabolism of Desulfovibrio vulgaris Hildenborough has provided several new datasets that might provide insights and constraints to the electron flow pathways. These datasets include (1) gene expression changes measured in microarrays for cells cultured with different electron donors and acceptors, (2) relative mRNA abundances for cells growing exponentially in defined medium with lactate as carbon source and electron donor plus sulfate as terminal electron acceptor, and (3) a random transposon mutant library selected on medium containing lactate plus sulfate supplemented with yeast extract. Studies of directed mutations eliminating apparent key components, the quinone-interacting membrane-bound oxidoreductase (Qmo) complex, the Type 1 tetraheme cytochrome c3 (Tp1-c3), or the Type 1 cytochrome c3:menaquinone oxidoreductase (Qrc) complex, suggest a greater flexibility in electron flow than previously considered. The new datasets revealed the absence of random transposons in the genes encoding an enzyme with homology to Coo membrane-bound hydrogenase. From this result, we infer that Coo hydrogenase plays an important role in D. vulgaris growth on lactate plus sulfate. These observations along with those reported previously have been combined in a model showing dual pathways of electrons from the oxidation of both lactate and pyruvate during sulfate respiration. Continuing genetic and biochemical analyses of key genes in Desulfovibrio strains will allow further clarification of a general model for sulfate respiration.